Effectiveness of Project-Based Learning in Improving Listening Competency among ESL Learners at a Malaysian TVET College - Noor Idayu Abu Bakar; Nooreen Noordin; Abu Bakar Razali (The English Teacher, 2019)
Listening plays a fundamental role as the first basic skill in English language communication but the skill seems to be neglected in ESL research and classrooms. The limited published studies in the literature reporting on the teaching of listening and the lack of details in the existing studies warrant more attention in finding more effective strategies to teach listening. Thus, the quasi- experimental study sought to ascertain the effectiveness of using project-based learning (PjBL) activities as a teaching strategy in improving the listening competency of ESL learners in a Communicative English course. Data were gathered from 44 students after a 16-week study conducted at a Malaysian TVET college. A PjBL teaching module comprising a number of listening activities was used in the experimental group as a treatment while the control group was taught using the conventional teaching strategy. A listening competency test was administered as pre-test and post-test on both groups. Data were analysed using t-tests, ANOVA and Tukey post hoc test. The study found that the learners in the PjBL group significantly outperformed those in the control group in their listening competency and dialogue listening comprehension with a large effect size. The study is important to increase the understanding of teachers and practitioners in the area of teaching of listening in ESL classrooms.